Distribution and quantitative analysis of homoanserine and its 2-oxo derivative in mouse tissues. (3rd June 2021) - Kakihana, Yuki; Kasamatsu, Shingo; Uchida, Koji; Ihara, Hideshi
Abstract: Imidazole-containing dipeptides (IDPs), such as carnosine and anserine, are endogenously produced and have been shown to function as antioxidants. Recently, we have characterized the endogenous production of 2-oxo-imidazole-containing dipeptides (2-oxo-IDPs), such as 2-oxo-carnosine, 2-oxo-anserine, and 2-oxo-homocarnosine in mouse tissues, including brain, and demonstrated that 2-oxo-IDPs exhibit higher antioxidant activities than the corresponding IDPs. In this study, we established a highly sensitive, specific, and quantitative method for the detection of the IDP homoanserine and its oxidized derivative 2-oxo-homoanserine via high-performance liquid chromatography tandem mass spectrometry coupled with a stable-isotope dilution method, and quantitatively analyzed its tissue distribution and age-related intra-brain distribution in C57BL/6J mice. The quantitative analysis revealed that homoanserine exists abundantly not only in the mouse brain but also in other tissues, such as the muscle and lungs. Further, we successfully detected the endogenous production of 2-oxo-homoanserine in the mouse brain. The mass spectrometric analysis revealed that homoanserine predominantly exists in the cerebrum and cerebellum and the concentrations in 10-week-old mice were approximately 50-fold higher than those in 1-week-old mice. Accordingly, this is the first study that reports the spatial and temporal expression patterns of homoanserine and its 2-oxo derivative in C57BL/6J mice.